Edukasi Pencegahan Bullying kepada Siswa SDN 01 Rasau Jaya Kubu Raya: Bullying Prevention Education for Students at SDN 01 Rasau Jaya Kubu Raya - Bambang Wijianto; Intan Yap; Risa Indriyani; Virna Helena Damanik; Inggrid Aprilia Manullang; Dimas Achmad Mu’arif (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Bullying in children can be classified as abnormal behavior that can affect the mental health of both the perpetrator and the victim. The village of Rasau Jaya I is a thriving transmigration area as a cultural, economic, and social center, including education with varied cultural, cultural, and social impacts. The Community Service Program (PKM) is designed to increase the knowledge of elementary students in grades 3 to 5 of SDN 01 Rasau Jaya in recognizing and preventing bullying in the school environment. This service program provides education using learning media such as posters and leaflets, lectures, question-and-answer discussions, and mini quizzes. The PKM program is conducted in groups, interactively and directly with students. Evaluation and monitoring activities were carried out using questionnaires (pre-test and post-test), which were analyzed descriptively and measured the ability of students to answer the questionnaire. The evaluation results show that there is an increase in the level of knowledge of students in recognizing and preventing bullying at school.